Eyebrows cue grandiose narcissism - Giacomin, Miranda; Rule, Nicholas O. (My University, 2018)
Objective: Though initially charming and inviting, narcissists often engage in negative interpersonal behaviors. Identifying and avoiding narcissists therefore carries adaptive value. Whereas past research has found that people can judge others’ grandiose narcissism from their appearance (including their faces), the cues supporting these judgments require further elucidation. Here, we investigated which facial features underlie perceptions of grandiose narcissism and how they convey that information. Method and Results: In Study 1, we explored the face’s features using a variety of manipulations, ultimately finding that accurate judgments of grandiose narcissism particularly depend on a person’s eyebrows. In Studies 2A–2C, we identified eyebrow distinctiveness (e.g., thickness, density) as the primary characteristic supporting these judgments. Finally, we confirmed the eyebrows’ importance in Studies 3A and 3B by measuring how much perceptions of narcissism changed when swapping narcissists’ and non-narcissists’ eyebrows between faces. Conclusions: Together, these data show that distinctive eyebrows reveal narcissists’ personality to others, providing a basic understanding of the mechanism through which people can identify narcissistic personality traits with potential application to daily life.
Keywords: eyebrows; face perception; narcissism; personality; person perception